2015
DOI: 10.3109/13880209.2015.1010738
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic acid exerts a neuroprotective effect in the kainate rat model of temporal lobe epilepsy: Underlying mechanisms

Abstract: RA could attenuate seizure, mitigates oxidative stress, augments the activity of defensive systems, and prevent hippocampal neuronal loss and MFS in the kainate model of TLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 39 publications
4
35
0
1
Order By: Relevance
“…High antioxidant activities including SOD, catalase and GSH have been detected in the brain in order to cope with oxidative stress damage . In animals with liver injury induced by ischaemia reperfusion, Hup‐A treatment elevated the activity of catalase, SOD, and GSH, but diminished the MDA concentration and thereby improved the hepatic ischaemia reperfusion injury in rats .…”
Section: Discussionmentioning
confidence: 99%
“…High antioxidant activities including SOD, catalase and GSH have been detected in the brain in order to cope with oxidative stress damage . In animals with liver injury induced by ischaemia reperfusion, Hup‐A treatment elevated the activity of catalase, SOD, and GSH, but diminished the MDA concentration and thereby improved the hepatic ischaemia reperfusion injury in rats .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, evidence has demonstrated the significant increase in the expression of the M1 microglial marker iNOS in a model of epilepsy induced by kainate in mice that causes severe damage to brain tissue [51] . Thus, we believe that the protective effect presented by RA in several experiments about neurodegenerative disorders, including the reduction of kainate-induced seizures [35] , may be caused by modulation of the M1-M2 microglial states, as shown here.…”
mentioning
confidence: 89%
“…Several biological activities are attributed to RA, such as antioxidant and anti-inflammatory properties and neuroprotective effects [26][27][28][29][30] . RA has been proven to be effective in experimental models of neurodegenerative diseases such as Alzheimer disease and amyotrophic lateral sclerosis [31,32] , and recently it was shown to have the interesting effect of reducing seizures in rats [27,[33][34][35] . A previous study showed that RA inhibits the activity of GABA-T.…”
mentioning
confidence: 99%
“…The chemical components of Spica Prunellae contain various bioactive compounds including triterpenes, flavonoids, phenolic compounds and carbohydrates (5)(6)(7)(8). Among these, oleanolic acid is associated with anticancer (9-11) and anti-inflammatory (12) properties, ursolic acid has shown anti-allergic and anti-inflammatory activities (11,13), rosmarinic acid has demonstrated antioxidant (14,15), neuroprotective (16,17) and anti-inflammatory effects (18), and polysaccharide has anticancer activity (19). As a whole, Spica Prunellae has also been reported to exhibit immunosuppressive activity (20), anti-angiogenic activity (21), vascular inflammation properties (22), anti-estrogenic activity (23), anti-HIV activity (24,25), and anticancer activity (19,26).…”
Section: Introductionmentioning
confidence: 99%